Integrons and Antiseptic Resistance Genes Mediate Resistance of Acinetobacter baumannii and Pseudomonas aeruginosa Isolates from Intensive Care Unit Patients with Wound Infections - Elkhatib, Walid F.; Khalil, Mahmoud A.F.; Ashour, Hossam M. (Current Molecular Medicine, 2019)
Background: Acinetobacter baumannii and Pseudomonas aeruginosa are of major concern for hospitalized patients. Methods: We evaluated antibiotic and antiseptic resistance of A. baumannii (n = 29) and P. aeruginosa (n = 37) isolates recovered from 66 intensive care unit (ICU) patients and determined the prevalence of qacE, qacEΔ1, and integrons in these clinical isolates. Antibiotic and antiseptic susceptibility testing was performed via Kirby Bauer disk diffusion and broth microdilution methods, respectively. The resistance genes and integrons were detected by PCR. A. baumannii and P. aeruginosa ICU isolates showed 100% and 70.3% antibiotic multiple drug resistance patterns, respectively. Results: The isolates also revealed high levels of resistance (MIC ≥ 16 μg/ml) against antiseptics commonly used in Egyptian hospitals (Benzalkonium, Benzethonium, and Chlorhexidine). The qacEΔ1 gene showed higher levels of prevalence in both A. baumannii and P. aeruginosa isolates (93.5% and 78%, respectively) as compared to that of qacE gene (52.0% and 33.0%, respectively). The intI1 was more prevalent among A. baumannii isolates (65.5%) compared to P. aeruginosa isolates (37.8%). P. aeruginosa resistance genotypes were significantly associated with antibiotic and antiseptic resistance patterns. A. baumannii resistance genotypes were associated with antiseptic-resistance patterns. Conclusion: The excessive usage of antiseptics may escalate bacterial resistance, especially with high prevalence of intI1 integron in these pathogens.
Keywords: wound infection